GTdownloader: A Python Package to Download, Visualize, and Export Georeferenced Tweets From the Twitter API - Juan Acosta-Sequeda; Sybil Derrible (Journal of Open Research Software, 2023)
This article describes GTdowloader, a Python package that serves as both an API wrapper and as a geographic information pre-processing helper to facilitate the download of Twitter data from the Twitter API. Specifically, the package offers functions that enable the download of Twitter data through single functions that integrate access to the API call parameters in the form of familiar Python functions syntax. In addition, the data is available for download in common formats for further analysis, which includes standard Geographic Information Systems (GIS) vector format. This software package is especially useful for users with little to no experience with building API calls but who would highly benefit from access to Twitter data.